The ANCHOR Framework: A Holistic Approach to Transdisciplinary and Regenerative Built Environment Education - Davey, Calayde (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This paper introduces the ANCHOR Framework, a transdisciplinary pedagogical model for Built Environment (BE) education, developed over a decade of iterative reflective practice (2020-2025). It addresses how conventional BE education, constrained by rigid, discipline-specific paradigms, leaves BE graduates ill- equipped for contemporary complex and systemic regenerative challenges. Utilising Schön’s reflective practices, the framework integrates ontological reframing (e.g., "waste" to "discards"), Lean practices, and systems thinking to cultivate paradigm agility. Data from practioner-led reflective cycles, student artefacts, and institutional feedback demonstrate enhanced student performance and disciplinary maturity. This pedagogy promotes cross-skilling, collaborative and transdisciplinary inquiry, and increase in student motivation for advanced, discipline-adjacent topics like circular economy or regenerative design. The ANCHOR Framework aims to prepare Built Environment graduates to move from siloed disciplinary thinking to actively navigating 'wicked problems' in interdisciplinary teams within transdisciplinary learning environments. This outcome of ANHOR aims to bridging the academic-industry gap by fostering collective adaptive reasoning and leadership for sustainable transformations. This practitioner-led reflection also highlights the need for broader applicability testing and further development.